Efeito de soluções desinfetantes sobre a estabilidade de cor de botões de íris artificiais nas cores azul e marrom obtidos por diferentes técnicas - Menezes, Fernanda Bimbato de [UNESP] (2012)
The color of the artificial iris with acceptable aesthetic is an important clinical condition for the rehabilitation of the eye. So, the present study was to investigate the influence of three disinfectant solutions on the color change of the artificial iris button obtained by different techniques for two-tone color. A total of 300 samples will be made by simulating artificial eyes. Samples were fabricated with either blue or brown color artificial iris. For each color, fifty samples of each technique (conventional (CE), prefabricated cap technique (PC) and inverted painting (IP)) will be made. For each technique, 10 samples will be subjected to three types of disinfectant solution (soap (NES), Opti-Free (OPF) and chlorhexidine 4% (CHX)), or remained without disinfection (control 1 (C1) will be immersed in saline and control 2 (C2) will be subjected to dry conditions). The disinfection procedure was performed during 120 days, and the disinfected samples were stored in saline solution during this period. The artificial iris color measurement was conducted through reflection spectrophotometry using the CIE L * a * b * after prosthesis polymerization, and after 60 and 120 days. The color change values increased over time. For both colors, ANOVA reveled significant difference on the color change values of the artificial iris button among technique and period; and disinfectant and period (P<0.01). CE e PC exhibited highest color stability for both color artificial iris. The artificial iris buttons disinfected with CHX exhibited highest color change significant compared to others disinfectants and control groups, independent the color. In conclusion, technique and disinfection/storage periods affected the artificial iris button